Pretension design of cable-network antennas considering the deformation of the supporting truss: A double-loop iterative approach. (1st May 2019) - Yuan, Pengfei; He, Baiyan; Zhang, Lianhong; Yuan, Zhe; Ma, Xiaofei
Highlights: Equal length algorithm for the form-finding of cable-networks is proposed. Compatible strategy between the cable-network and the supporting truss is proposed. An iterative approach for the form-finding of cable-network antennas is proposed. The advantages of the proposed approach are demonstrated by two case studies. Abstract: Cable-network structures are usually adopted as an ideal form of satellite antennas. The performance of cable-network antennas crucially depends on the surface accuracy and the tension distribution. In some cases, conventional algorithms, such as the equal tension algorithm and the equal force density algorithm, may lead to the decrease of the effective region. Thus the equal length algorithm based on the force density method is proposed in this paper. In this algorithm, the free nodes are restricted as close as possible to their desired positions, which ensures the area of the effective region and the high surface accuracy. The cable tensions are restricted by the maximum tension ratios, which ensures the uniform tension distribution. Furthermore, the elastic deformation of the supporting truss seriously affects the antenna's performance. Therefore, a double-loop iterative form-finding approach for the cable-network antenna with flexible supporting truss is proposed to find a pre-tensioned configuration that meets the requirements of the surface accuracy and the tension distribution. Firstly, an inner loop based on the equal length algorithm is established for the form-finding of the cable-network. Through this inner loop, the high surface accuracy and the uniform tension distribution can be achieved. Secondly, a compatible strategy between the cable-network and the flexible supporting truss is proposed. Through this strategy, a nonlinear finite element (FE) model of the cable-network antenna is established to capture the compatible deformation. Thirdly, an outer loop combining the equal length algorithm and the compatible strategy is established, in which the node coordinates and the cable tensions are iteratively fed to the force density model and the FE model in steps 1 and 2. Through this outer loop, the compatible deformation is fully considered. The whole loop will stop and converge to a reasonable solution of the surface accuracy and the tension distribution within given criterions. Numerical examples of an offset cable-network antenna are provided, and the results are compared with previous literature.